Pengembangan Pengelolaan Kelas dalam Meningkatkan Efisiensi Pembelajaran Pendidikan Agama Islam (PAI) - Mohammad Riza Zainuddin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2016)
The decentralized system of education in this era give a chance to each school institutions to improve the quality of schools that participate in improving the quality of education responded by seeking to every teacher to be creative to improve classroom management appropriately for learning run efficiently and effectively. Arguing that the media class is meeting all the educational component as well as the cutting edge and also educational base. This class management concept seeks to provide a solution to the problem in the class, whose scope is not limited to delivery of content, but also includes some things thoroughly to organize classes include: first academic activities such as planning, implementation and assessment of learning. Both administrative activities that include activities such as procedural and organizational arrangement of the room, grouping students in the division of tasks, classroom discipline, the procurement of test, organizing classes, reporting. So the concept of classroom management is trying to empower the potential of existing classes as optimally as possible to support the process of educational interaction in achieving learning goals that are particularly effective in the material Islamic Education.